Seizing the future : - Zey, Michael G. (Simon & Schuster, 1994)
A thought-provoking, optimistic look at future trends in society discusses the positive impact of the revolution in science, technology, and industry on culture, medicine, education, health, and other fields of human endeavor. 30,000 first printing.